Scattering of spherically symmetric d-dimensional α′−corrected black holes in string theory - Moura, Filipe (2013)
We study scattering of minimally coupled massless scalar fields by non-extremal spherically symmetric black holes in d dimensions with string-theoretical α′ corrections. We then obtain a formula for the low frequency absorption cross section for every black hole of this kind, which we apply to known black hole solutions. We compare the α′ corrections for the absorption cross section with those for the black hole entropy, obtained through Wald’s formula, in each case concluding that these corrections are different. We find a general covariant formula for the absorption cross section including α′ corrections, in terms of the horizon area and temperature